A new step-up DC-DC converter topology using switched inductor and switched capacitor networks for high negative DC voltage applications - Clement Raj, A.; Bensraj, Ramaiyan (Institute of Advanced Engineering and Science, 2024)
This study presents a novel topology for a high-gain Cuk converter without isolation, leveraging switched-inductor (SL) and switched-capacitor (SC) networks tailored for renewable energy sources. Unlike traditional Cuk converters that perform negative-to-positive boost DC-DC voltage conversion, this innovative design offers a significantly enhanced voltage-boosting capacity. They evolve from the conventional Cuk converter by integrating an SL instead of the singular inductor and substituting the energy-transferring capacitor with an SC. The standout benefits of the modified Cuk converters include a remarkable voltage conversion ratio and minimized voltage stress on the primary switch, allowing a low-voltage-rated switch for greater efficiency. Comparatively, the proposed designs surpass the classical Cuk and a few modified Cuk converters in voltage gain and reduced switch voltage stress. The converter also avoids the need for transformers or coupled inductors, resulting in minimized volume, loss, and expense. The converters' operation in continuous conduction mode is rigorously analyzed in this study. After deriving all the relevant equations, they are validated against outcomes. The proposed Cuk converter topology was simulated using the MATLAB/Simulink tool, and the findings are deliberated. The performance of the proposed converter is compared with the other converters, and the proposed converter's superiority is proved through the obtained results.